Dose–response relationship between alcohol consumption and workplace absenteeism in Australia - Marzan, M.B.; Callinan, S.; Livingston, Michael; Jiang, H. (2023)
Introduction: Workplace absenteeism is a burden in Australia. The estimated productivity losses due to alcohol were around $4.0 billion in 2017, with absenteeism driving 90% of these costs. We aim to determine the dose–response relationship between average daily alcohol consumption and heavy episodic drinking (HED) frequency and workplace absenteeism amongst Australian workers. Methods: We used the 2019 National Drug Strategy Household Survey of Australian employed workers aged ≥20 years to 69 years old. Respondents' average daily alcohol consumption was categorised into four: abstainers, light to moderate (1–20 g of alcohol/day), risky (>20–40 g of alcohol/day) and high-risk (>40 g of alcohol/day). HED was classified into four frequency measures (never, less than monthly, monthly, weekly). The outcome variables came from dichotomised measures of: (i) absence due to alcohol consumption; and (ii) broader sickness absence–absence due to illness or injury in the previous 3 months. Results: Risky (adjusted odds ratio 4.74 [95% CI 2.93–7.64]) and high-risk drinking (adjusted odds ratio 6.61 [95% CI 4.10–10.68]) were linked to increased odds of alcohol-related absence. Higher HED frequency was significantly associated with alcohol-related and broader sickness absenteeism. No significant associations exist between regular alcohol consumption and broader sickness absence in fully adjusted models. Discussion and Conclusions: Findings suggest that only HED is linked to broader sickness absence. However, there is a strong dose–response association between alcohol consumption and alcohol-related absences for both consumption measures amongst Australian workers. Population-level policies that reduce alcohol consumption to moderate level and less frequent HED might address workplace absenteeism.